Cotranscription and processing of 23S, 4.5S and 5S rRNA in chloroplasts from Zea mays. - Strittmatter, G (1984)
The termini of rRNA processing intermediates and of mature rRNA species encoded by the 3' terminal region of 23S rDNA, by 4.5S rDNA, by the 5' terminal region of 5S rDNA and by the 23S/4.5S/5S intergenic regions from Zea mays chloroplast DNA were determined by using total RNA isolated from maize chloroplasts and 32P-labelled rDNA restriction fragments of these regions for nuclease S1 and primer extension mapping. Several processing sites detectable by both 3' and 5' terminally labelled probes could be identified and correlated to the secondary structure for the 23S/4.5S intergenic region. The complete 4.5S/5S intergenic region can be reverse transcribed and a common processing site for maturation of 4.5S and 5S rRNA close to the 3' end of 4.5S rRNA was detected. It is therefore concluded that 23S, 4.5S and 5S rRNA are cotranscribed.